Several Sociolinguistic Particularities of French-English Bi-Lingualism in Canada - V. D. Melnikova; L. A. Ulianitckaia (Дискурс, 2023)
Introduction. The relevance of the study is explained by the necessity to preserve Frenchspeaking culture and language on the territory of Canada in the conditions of globalization, the spread of American mass culture and the significant impact of English as a global language. The purpose of the work is to describe and analyze the sociolinguistic particularities of the existence of the French language in the English-speaking competitive environment in Canada.Methodology and sources. During the study, the following sociolinguistic methods were used: descriptive method, comparison method, continuous sampling method, sociolinguistic analysis method, quantitative data processing method, questionnaire survey. The research is based on the material of Сanadian media, legislative acts regulating the state's language policy, data obtained through surveys of Canadian citizens, and 5,234 inscriptions in five Canadian cities which were selected to examine the country's linguistic landscape.Results and discussion. Under Canadian laws, French and English have equal status in parliamentary readings, in public services and in everyday life, as well as in education, radio and television. However, English is the dominant language and has great prestige throughout Canada. All of the evidence collected shows the decisive superiority of English as the primary means of communication in media, advertising and politics. Existing legislation to protect and promote the use of both official languages is not fully enforced, as evidenced by numerous complaints from Canadians to the Commissioner of Official Languages.Conclusion. In Canada, a multi-component exoglossic linguistic situation has developed with two official languages – English and French, which is characterized by the existence of natural bilingualism. Linguistic minorities, such as Anglophones in Quebec and Francophones outside Quebec, may experience linguistic discrimination, creating tensions between residents of the same country. French is significantly influenced by the majority English and immigrant languages that dominate the linguistic landscape of Canadian cities.